THE ISLAMIC EDUCATION METHODS AS AN EFFORT TO STRENGTHEN RELIGIOUS MODERATION IN ELEMENTARY SCHOOLS - Nazopah, Nada; Fadli, Adi (Al-Mubin, 2025)
It is essential to teach religious moderation from an early age so that conflicts that occur in society can be adequately handled. Through Islamic education, which is rahmatan lil'alamin, educational institutions such as schools are expected to be the forerunner of children's character building and provide an understanding of religious moderation so that children are accustomed to responding to occurring differences. This paper aims to discuss educational methods teachers can use to teach students about religious moderation, especially at the elementary school level. This paper is a literature study by collecting data from various literature and information from available sources such as books, journals, reports, and other documents. The cultivation of religious moderation education in elementary schools is carried out by integrating the values of religious moderation education into each existing subject and adjusting to the material being taught. Islamic education methods that can be used in its implementation include character education with the promotion method, dialogue learning and inclusive education, problem-based approach with the qhisah or story method, case study with the method of amtsal or parable, as well as field experience, qudwah or exemplary method and habituation